IBM KELOMPOK USAHA SOUVENIR SABLON DIGITAL - Krisnawati, Maria; Prasetyaningtyas, Wulansari; Mujiyono, Mujiyono (Universitas Negeri Semarang, 2015)
Targets to be achieved through IbM is on aspects of production and management. Aspects of the production which increased the production technology of making souvenirs, increasing capacity in the field of design through the program Corel Draw and Adobe Photoshop as well as consolidation of production procedures with due regard to health and safety work management. Management aspects namely on financial management, financial management hold good with regular bookkeeping, through marketing management produces forms of promotion through various media. Market network expansion and facilitate consumer access to order products.Through HR management can improve the training of human resources, the provision of entrepreneurial motivation and self empowerment. IbM implemented through phases 1 ) Preparation ; 2 ) Stage Assessment ; 3 ) The Plan or Program Activity; 4 ) Phase Action Plan ; 5 ) Implementation Phase or activity ; and 6 ) Evaluation Phase . It is expected to be implemented through the stages can help solve problems and realize the needs of partners.